Multiperiod Analysis of Adoption Motives: The Case of SFAS No. 106 - Amir, Eli; Livnat, Joshua (The Accounting Review, 1996)
[This study examines managers' adoption-timing motives related to SFAS No. 106. Results suggest that firms attempt to correct the market's perception of the magnitude of the postretirement benefit (PRB) obligation by choosing early adoption. We find that 1991 adoptors of SFAS No. 106 had lower unexpected PRB liabilities than 1992 adoptors, who in turn had lower unexpected liabilities than 1993 adopters. Earnings management is also considered as a motive for adoption-timing. Many firms adopt the standard in the year (and quarter) with the lowest pre-SFAS No. 106 earnings. Finally, we consider PRB renegotiation efforts as a motive for delaying adoption and find that 1992 and 1993 adopters are indeed more likely than 1991 adopters to reduce PRB obligations by negotiating a plan amendment.]